Distribution of Cannabinoid Receptors in Keratinocytes of Healthy Dogs and Dogs With Atopic Dermatitis - Chiocchetti, Roberto; De Silva, Margherita; Aspidi, Francesca; Cunha, Rodrigo Zamith; Gobbo, Francesca; Tagliavia, Claudio; Sarli, Giuseppe; Morini, Maria (Frontiers in Veterinary Science, 2022)
It is commonly accepted that some form of skin barrier dysfunction is present in canine atopic dermatitis (AD), one of the most common cutaneous pruritic inflammatory diseases of dogs. The impaired skin barrier function facilitates the penetration of allergens and subsequently stronger sensitization responses. The role of the endocannabinoid system (ECS) in the physiology and pathology of the skin is becoming increasingly established. It has been demonstrated that cannabinoid receptors are expressed in healthy and diseased skin and, based on current knowledge, it could be stated that cannabinoids are important mediators in the skin. The present study has been designed to immunohistochemically investigate the expression of the cannabinoid receptors type 1 (CB1R) and 2 (CB2R) and the cannabinoid-related receptors G protein-coupled receptor 55 (GPR55), transient receptor potential vanilloid 1 (TRPV1) and ankyrin 1 (TRPA1), peroxisome proliferator-activated receptors alpha (PPARα), and serotoninergic receptor 1a (5-HT1aR) in keratinocytes of healthy dogs and of dogs with AD. Samples of skin tissues were collected from 7 healthy controls (CTRL-dogs) and from 8 dogs with AD (AD-dogs). The tissue samples were processed using an immunofluorescence assay with commercially available antibodies, and the immunolabelling of the receptors studied was quantitatively evaluated. The keratinocytes of the CTRL- and the AD-dogs showed immunoreactivity for all the receptors investigated with a significant upregulation of CB2R, TRPV1, TRPA1, and 5-HT1aR in the epidermis of the AD-dogs. The presence of cannabinoid and cannabinoid-related receptors in healthy keratinocytes suggested the possible role of the ECS in canine epidermal homeostasis while their overexpression in the inflamed tissues of the AD-dogs suggested the involvement of the ECS in the pathogenesis of this disease, having a possible role in the related skin inflammation and itching. Based on the present findings, the ECS could be considered a potential therapeutic target for dogs with AD.